Disability in Multicultural Theory: Conceptual and Social Justice Issues. (June 2016) - Anastasiou, Dimitris; Kauffman, James M.; Michail, Domna
Multicultural theorists in education tend to treat disability as part of cultural diversity and apply a minority group model to disability rights. We critically examine the fundamental presuppositions and social justice issues behind this assimilation of disability into a multicultural frame of reference. The implications of the neutralization of disability are discussed. Reasons for reconciling different views of special education and multicultural education to better achieve social justice are detailed. Policy implications of noting the differences between people with disabilities and minority groups are suggested.